(untitled) (Global Journal of Human-Social Science, 2024)
The incorporation of information technologies has transformed capitalist relations directly impacting the forms of subsumption and the realization of work This article proposes a critical analysis of the changes caused by these technologies arguing that they intensify capitalist relations rather than represent a rupture with the logic of value as suggested by neofeudal theses The insertion of ICT is not a natural technological development but rather an imposition of class struggle within the capitalist logic The new forms of control and disciplining of labor create an illusion of self-realization obscuring exploitation and expropriation as the real objectives of these technological transformations